ANALISA KUALITAS AIR (FISIK, KIMIA) SEBAGAI INDIKATOR KEHIDUPAN INDUK IKAN NILA (Oreochromis niloticus) DI LOKA BUDIDAYA AIR TAWAR MANDIANGIN - Sofarini, Dini (Bumi Lestari; Vol 9 No 1 (2009), 2009)
This research is aimed to find out water quality in ponds at freshwater plantation world, that was whether fit or not with Water Quality Standard. Besides, the research was aimed to identify about accomplishment of water quality management at freshwater plantation world Mandiangin. The research was hoped could contribute to provide updated information for the direction of freshwater plantation world Mandiangin about the condition of water quality in ponds. Result of the research showed that physics and chemist parameters were fit with the condition of Water Quality Standard (classified C), that was for fisheries and farming needs, acceptable for Dissolved Oxygen that had a lower grade and did not fit with Water Quality Standard. Besides, accomplishment of water quality management was good enough. Especially for DO, it might need aerator to increase DO values.
Keywords: water quality; physics and chemist parameters; pond; freshwater